Das Opfer nach der Sintflut für die Gottheit(en) des Alten Testaments und des Alten Orients: Eine neue Deutung - Baumann, Gerlinde (Verbum et ecclesia, 2013)
The Sacrifice for (the) God(s) after the Flood in Ancient Israel and the Ancient Near East: A New Interpretation. The experience of a large, devastating flood is part of the cultural heritage of mankind. The famous ‘texts of the deluge’ come from Mesopotamia. Here, the flood tradition dates back to the 3rd Millennium. The longest and most traditional of these texts, which - amongst other things - deal with the interpretation of these events, is the Atramḫasis myth. The literary-dependent text is the Gilgamesh epic, and the Old Testament version is the story of the Flood that is found in Genesis 6-9. For a long time the similarities and differences between these three texts have been known. However, so far little attention was given to a passage that all three texts share: the sacrifice of the surviving humans after the Flood. The reaction of the deity(ies) differs in these three texts. In this article I would like to consider the similarities and differences between the texts in order to evaluate the significance of the Old Testament text. This is against the background of recent insights in the field of ancient Israelite sacrifice, related to cultural anthropology. These three passages are first considered in their context and then compared to the relevant aspects of each other before a conclusion is drawn.